2022
DOI: 10.1186/s13741-022-00246-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical covariates that improve surgical risk prediction and guide targeted prehabilitation: an exploratory, retrospective cohort study of major colorectal cancer surgery patients evaluated with preoperative cardiopulmonary exercise testing

Abstract: Background Preoperative risk stratification is used to derive an optimal treatment plan for patients requiring cancer surgery. Patients with reversible risk factors are candidates for prehabilitation programmes. This pilot study explores the impact of preoperative covariates of comorbid disease (Charlson Co-morbidity Index), preoperative serum biomarkers, and traditional cardiopulmonary exercise testing (CPET)-derived parameters of functional capacity on postoperative outcomes after major color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…It has been shown that surgical patients with anaemia carry an increased risk of postoperative complications and have a higher mortality rate than those without this condition (Bolshinsky et al 2022 ). Treating anaemia before surgery reduces the number of postoperative complications and blood transfusions (Blum et al 2022 )(Froessler et al 2016 ) and accelerates the recuperation of mobility [s39].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that surgical patients with anaemia carry an increased risk of postoperative complications and have a higher mortality rate than those without this condition (Bolshinsky et al 2022 ). Treating anaemia before surgery reduces the number of postoperative complications and blood transfusions (Blum et al 2022 )(Froessler et al 2016 ) and accelerates the recuperation of mobility [s39].…”
Section: Discussionmentioning
confidence: 99%
“…The Measurement of Exercise Tolerance before Surgery (METS) trial ( n = 1400) reported no added prognostic value of VO 2peak in predicting 30‐day mortality or myocardial infarction 42 . In major colorectal cancer surgery variables derived from CPET, in addition to VO 2peak , (VCO 2 kinetics) added significantly to the prediction of poorer postoperative outcomes 48 . With the aim of reducing burden for patients, clinicians, researchers, and the health care system, the 6MWT and 30STS are both valid and feasible measures of exercise capacity in populations with cancer and could be used either in lieu of having access to CPET or as initial screening to determine if an individual is high risk and requires further assessment using CPET.…”
Section: Discussionmentioning
confidence: 99%
“…42 In major colorectal cancer surgery variables derived from CPET, in addition to VO 2peak , (VCO 2 kinetics) added significantly to the prediction of poorer postoperative outcomes. 48 With the aim of reducing burden for patients, clinicians, researchers, and the health care system, the 6MWT and 30STS are both valid and feasible measures of exercise capacity in populations with cancer and could be used either in lieu of having access to CPET or as initial screening to determine if an individual is high risk and requires further assessment using CPET. Further evidence is required to establish concurrent validity given correlations between these measures and CPET variables were only fair to moderate.…”
Section: F I G U R Ementioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] There are increasing evidence demonstrating multidisciplinary prehabilitation programs that improve functional capacity before surgery may reduce hospital LOS after cancer surgery. [15][16][17][18][19] Prolonged length of stay (LOS) occurs in approximately 10% of patients undergoing major upper GI surgery and is associated with higher risks of readmission, postoperative complications, and mortality.…”
Section: Introductionmentioning
confidence: 99%